Social Capital to Harmonise the Health of Rowdy Cattle Farmers and the Environment during the Covid-19 Pandemic in Hamparan Perak District of Deli Serdang Regency of Indonesia - Wasito , .; Bakrie, Bachtar; Hutahaean, Lintje; Khairiah , .; Simatupang , Sortha; Sukardi , . (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 5, 2023)
Building social capital is crucial for rowdy cattle producers and wealthy landowners because it fosters the emotional ties necessary for a mutualistic symbiosis. Eid al-Adha is a holiday for Muslims in which there is an obligation to slaughter sacrificial animals, an opportunity for rowdy cattle farmers and sacrificial animal providers in Klambir Village V Kebun and Klumpang Kebun, Hamparan Perak District, Deli Serdang Regency. The research in the two villages aimed to analyse the strengthening of social capital, which can harmonise the health of humans, cows, and the environment. A descriptive study was carried out in 2021 and 2022, with a pattern of observation in the field, direct interviews with focused discussion methods, and in-depth interviews with rowdy cattle farmers to obtain primary data (2019-2022). This study showed harmony between the role of social capital in the health of the business with rowdy cows and the environment. This type of activity has been running since 2016. Mutualism symbiosis is manifested due to mutual trust between farmers and owners of capital to obtain profits; and strengthen both parties' social interaction and economic income. In addition, there was an increase in demand for the number of sacrificial animals during 2019-2022, except for 2020, there was a decrease in sales of around 20 per cent due to the implementation of restrictions on community activities (IRCA) because of the Covid 19 pandemic.